Strengthening Traditional Medicine Systems in Nepal through Chemical and Pharmacological Research - Devkota, Hari Prasad; Devkota, Anjana Adhikari; Kaundinnyayana, Atisammodavardhana; Bhandari, Dhaka Ram (Annapurna Journal of Health Sciences, 2023)
Medicinal plants are an integral part of traditional medicine systems all over the world. Nepal, rich in biodiversity and ethnic, linguistic, and cultural diversity, possesses different traditional and folk medicinal practices for thousands of years. These systems have been using many locally available medicinal plants as crude drugs, which are not always properly documented. Detailed documentation and research related to the conservation and cultivation of medicinal plants should be carried out. Scientific studies related to chemical analysis, standardization, evaluation of pharmacological activities, and safety should be carried out to strengthen these systems of traditional medicine. Adequately designed clinical studies are necessary to provide evidence for their therapeutic efficacy.